Active Surveillance of the Safety of Medications Used During Pregnancy. Issue 6 (11th January 2021) - Huybrechts, Krista F; Kulldorff, Martin; Hernández-Díaz, Sonia; Bateman, Brian T; Zhu, Yanmin; Mogun, Helen; Wang, Shirley V
Abstract: The scientific community relies on postmarketing approaches to define the risk of using medications in pregnancy because information available at the time of drug approval is limited. Most studies carried out in pregnancy focus on a single outcome or selected outcomes. However, women must balance the benefit of treatment against all possible adverse effects. We aimed to apply and evaluate a tree-based scan statistic data-mining method (TreeScan; Martin Kulldorff, Harvard Medical School, Boston, Massachusetts) as a safety surveillance approach that allows for simultaneous evaluation of a comprehensive range of adverse pregnancy outcomes, while preserving the overall rate of false-positive alerts. We evaluated TreeScan with a cohort design and adjustment via propensity score techniques, using 2 test cases: 1) opioids and neonatal opioid withdrawal syndrome and 2) valproate and congenital malformations, implemented in pregnancy cohorts nested within the Medicaid Analytic eXtract (January 1, 2000–December 31, 2014) and the IBM MarketScan Research Database (IBM, Armonk, New York) (January 1, 2003–September 30, 2015). In both cases, we identified known safety concerns, with only 1 previously unreported alert at the preset statistical alerting threshold. This evaluation shows the promise of TreeScan-based approaches for systematic drug safety monitoring in pregnancy. A targeted screening approach followed by deeper investigation to refine understanding of potential signals will ensure that pregnant women and their physicians have access to the best available evidence to inform treatment decisions.